Morphological and Molecular Cytogenetics Analyses for a Newly Natural Hybridization in Campeiostachys kamoji and Leymus duthiei of Triticeae - Wu, Dan-Dan; Zhou, Shi-Qi; Zhao, Yu-Xin; Bao, Jun-Hao; Zheng, Ting-Ting; Pan, Xiao-Yang; Li, Ying-Hui; Xu, Li-Li; Zhu, Wei; Cheng, Yiran; Sha, Li-Na; Wang, Yi; et al. (Phytotaxa, 2025)
Natural hybrids in Triticeae have been frequently reported from the sympatric species with at least one same sub-genome, or within species containing the same genome constitution in the Qinghai-Tibet Plateau at relative high altitudes. The natural hybrids have seldom been reported between species having completely different genome constitutions and distant phylogenetic relationships. We collected a plant HY2301 and assumed that it was a hybrid, based on the sterile pollen with inviability, and intermediate morphological characters with companion species. In this study, we performed morphology, cytogenetics, microscopy tissue, and phylogenetic analyses to investigate the genome constitution and origination. The results showed that: (1) morphologically, the spike of the hybrid HY2301, such as the spike length, the presence of glumes with awns, is similar to that of Campeiostachys kamoji, while it possesses awn and lemma in nearly equal length, and yellow anthers, which are similar to those of Leymus duthiei; (2) cytogenetically, sterile plants HY2301 is a pentaploid with 35 chromosomes (2n= 5x =35), consisting of the StYHNsXm genome, with abnormal male gamete development and mature embryo sac development; (3) the Campeiostachys kamoji with the StStYYHH genome and Leymus duthiei with the NsNsXmXm genome served as the maternal and paternal donors, respectively. Interestingly, genetic affinity exists between the St and Y sub-genomes in the hybrids and is paired as bivalent during the pollen mother cell (PMC) metaphase I stage. In summary, HY2301 is a pentaploid natural hybrid with StYHNsXm genome between two sympatric companion species, viz. the hexaploid Campeiostachys kamoji and the tetraploid Leymus duthiei, which serve as the maternal and paternal donor respectively. This study provides another case of natural hybridization, which provides new insights for understanding species origination and evolution in the tribe Triticeae.